2014
DOI: 10.1063/1.4900511
|View full text |Cite|
|
Sign up to set email alerts
|

Microscopic mechanism of electron transfer through the hydrogen bonds between carboxylated alkanethiol molecules connected to gold electrodes

Abstract: The atomic structure and the electron transfer properties of hydrogen bonds formed between two carboxylated alkanethiol molecules connected to gold electrodes are investigated by employing the non-equilibrium Green's function formalism combined with density functional theory. Three types of molecular junctions are constructed, in which one carboxyl alkanethiol molecule contains two methylene, -CH2, groups and the other one is composed of one, two, or three -CH2 groups. Our calculations show that, similarly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…As can be seen from Table , the dihedral angle and the Mulliken charge have obvious changes as compared to other geometric parameters. For CTP-H without metal ions, the dihedral angle, ϕ, is 179.8°, displaying a coplanar cyclic configuration, the same as that reported previously . However, the coordination structure might be changed, while a bivalent metal ion is applied to replace the two protons.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…As can be seen from Table , the dihedral angle and the Mulliken charge have obvious changes as compared to other geometric parameters. For CTP-H without metal ions, the dihedral angle, ϕ, is 179.8°, displaying a coplanar cyclic configuration, the same as that reported previously . However, the coordination structure might be changed, while a bivalent metal ion is applied to replace the two protons.…”
Section: Resultssupporting
confidence: 71%
“…Recently, many studies focus on the electronic properties as well as the transportation behavior of systems with noncovalent interactions, including hydrogen bond (H-bond), π–π stacking, and electrostatic interactions. Since the H-bond is ubiquitous in both biological and self-assembling materials, electron transportation of H-bond-mediated systems has gained great attention. Nishino et al have studied experimentally the electron transport behavior of H-bonds formed in two carboxylated alkanethiol molecules (SC n COOH//HOOCC n S) and found that it conducts electrons better than a covalent σ-bond at a short range; however, the conductance decays rapidly with the increase of molecular length. , Hou et al have studied the conductance of carboxylated alkanethiol molecules by first-principles calculations, and they attributed the high conductance of H-bonded systems to the presence of resonance in the transmission near Fermi energy . The inclusion of this observation is essential in understanding the electron transport behavior of H-bond-mediated systems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first contracted the molecular junctions by the AuÀ S bond distance until about 2.30-2.40 Å, corresponding to the sulfur atom binding at the top site. [37,[42][43][44][45] Following contraction, we pulled them apart gradually, until the bond fission occurred. In the stretching process, we obtained a series of optimized structures at given distances, as shown in Supporting Information, and built the relationship between the distance and total electronic energy, stretching force, and molecular conductance.…”
Section: Theoretical and Computational Detailsmentioning
confidence: 99%
“…An alternative theoretical explanation to this finding was given by Li et al, who took into account an explicit self-energy correction in their calculations. 13 In a more general context, our results are also relevant for the issue of understanding the role of the chemical bond in electron transfer and transport processes. In this connection, high-level calculations are required to account both for the electronic structure of weakly bonded systems and transport properties.…”
mentioning
confidence: 89%